2017
DOI: 10.21037/jtd.2017.05.74
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of perforin in CD8+ T lymphocytes in patients with Mycobacterium tuberculosis infection and its potential value as a marker for efficacy of treatment

Abstract: Our results show that expression of perforin in CD8 T lymphocytes is downregulated in PTB infection and ESAT-6 and CFP-10 peptides might participate in the downregulation process. This finding cautiously suggests that MTB Ag-stimulated perforin downregulation and IFN-γ upregulation might be a potential index for monitoring therapy response in active PTB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Similarly, lower expression of other immune subset genes (such as NK marker NCAM1) in blood in TB patients may also relate to migration of lymphocytes or natural killer cells from the peripheral blood to the site of infection [32]. Furthermore, GNLY and PRF1 expression levels were also significantly lower in TB patients compared to TST+ and TST- individuals, which is consistent with published data [33,34] and might be explained by rapid consumption of both perforin and granulysin during active disease due to an ongoing effector immune response, or due to migration of the T cell subset responsible for its production [35].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, lower expression of other immune subset genes (such as NK marker NCAM1) in blood in TB patients may also relate to migration of lymphocytes or natural killer cells from the peripheral blood to the site of infection [32]. Furthermore, GNLY and PRF1 expression levels were also significantly lower in TB patients compared to TST+ and TST- individuals, which is consistent with published data [33,34] and might be explained by rapid consumption of both perforin and granulysin during active disease due to an ongoing effector immune response, or due to migration of the T cell subset responsible for its production [35].…”
Section: Discussionsupporting
confidence: 88%
“…Cytotoxic molecules, notably granzyme B secreted by cytolytic T cells, contribute in a major way to protection against TB . In order to study the granzyme B as a potential biomarker for TB, we measured by ELISA the granzyme B levels in the supernatants of PBMCs from the LTBI individuals versus aTB patients in response to PPD, ESAT‐6 and Rv0140.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of IFN‐γ, granzyme B, and perforin in CD8+ T lymphocytes during the different disease phases of Mtb infection has been evaluated before and after stimulation with ESAT‐6 and CFP‐10. Positive down‐regulation of perforin and granzyme B after stimulation with ESAT‐6 and CFP‐10 peptides in aTB was seen using ICS . Moreover, it has been shown that protection from reactivation in nonhuman primate model was mainly correlated with enhanced CD8+ T cell‐function and high granzyme B secretion .…”
Section: Discussionmentioning
confidence: 96%
“…Our results support the recent findings on the higher IFN-γ production by stimulated PBMCs with PPD in patients with infiltrative TB compared to other clinical features of TB and healthy controls [24]. Moreover, the increased IFN-γ production from PBMCs of pulmonary TB patients upon stimulation with either early secretory antigenic target of 6 kDa (ESAT6) or culture filtrated protein 10 (CFP10), and the high expression of IFN-γ by CD4+ T cells and CD8+ T cells have been recently demonstrated [39].…”
Section: Discussionmentioning
confidence: 96%